Detailaufnahme vom Ulli Beier-Schrein, Doppelaxt des Gottes Shango (Of Art Worlds - Collecting and Archiving Modern and Contemporary Art on the African Continent, 2014)
Copyright held by Iwalewahaus, CBCIU.
Keywords: Africa; Art; Interior decoration; Artists; Orisha religion; Yoruba (African people)--Religion; Yoruba (African people); Sculpture; Photographs; Shrine; Shango; Yoruba Art; Orisha; Orisha Art; Art Collector; Art Collecting; Wood Sculpture